Lithium ion battery positive electrode active material and preparation method thereof
By using the electrochemical reaction of oxidized polyaniline after oxidation and alkali treatment with lithium-ion electrolyte in lithium-ion batteries, the problem of low specific capacity of the positive electrode active material is solved, and a high specific capacity and environmentally friendly battery material preparation is achieved.
Patent Information
- Application Number
- CN202410884198.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-03
- Publication Date
- 2024-12-13
AI Technical Summary
The specific capacity of the positive electrode active material of existing lithium-ion batteries is relatively low, which limits the application performance of the battery.
Polyaniline, oxidant and water are mixed with a positive electrode active material to adjust the pH value to acidicity to perform oxidation reaction, obtain oxidized polyaniline, and mixed with an alkaline solution to form intrinsic oxidized polyaniline, assembled with a lithium ion-containing electrolyte as a positive electrode active material , through electrochemical reduction, lithium ions are embedded in the polyaniline molecular chain to form a stable charge storage site.
The specific capacity of the positive electrode active material is improved and the charge storage capacity is achieved. At the same time, the method is economical and environmentally friendly, avoiding toxic raw materials and high-temperature heating, and is suitable for daily preparation.
Smart Images

Figure CN119119458A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular, relates to a positive electrode active material for a lithium ion battery and a preparation method thereof. Background Art
[0002] With the increasing demand for energy and the continuous improvement of social and economic sustainable development, green energy with high performance and low cost has attracted more and more attention. In 1977, Macdiarmid, Heeger and Shirakawa first synthesized conductive polymers. Since conductive polymers can undergo reversible redox reactions, they can be used as battery active materials to make polymer batteries. Polymer batteries have developed rapidly due to their advantages such as rechargeability, long life, non-toxicity and environmental protection. In particular, the use of polyaniline as the positive electrode active material of secondary batteries has become a hot topic in polymer battery research in recent years because of its advantages such as easy availability of materials, low price, ability to polymerize in aqueous solution, good stability, light weight, small discharge, storage resistance, and high number of cycles. Although hard carbon materials have many advantages, their low specific capacity limits their application in batteries.
[0003] Therefore, current positive electrode active materials still need to be improved. Summary of the invention
[0004] The present invention aims to solve one of the technical problems in the related art at least to a certain extent. To this end, one object of the present invention is to provide a positive electrode active material for a lithium ion battery and a preparation method thereof, wherein the positive electrode active material prepared by the method provided in the present application has a high specific capacity.
[0005] In the first aspect of the present invention, the present invention proposes a method for preparing a positive electrode active material for a lithium ion battery. According to an embodiment of the present invention, the method includes: mixing polyaniline, an oxidant and water, adjusting the pH value to acidic, and performing an oxidation reaction to obtain oxidized polyaniline; mixing the oxidized polyaniline and an alkaline solution to react to obtain an intrinsic oxidized polyaniline; preparing a positive electrode using the intrinsic oxidized polyaniline as a positive electrode active material; using a solution containing lithium ions as an electrolyte, assembling an electrochemical cell with the positive electrode, and performing electrochemical reduction so that lithium ions are doped into the intrinsic oxidized polyaniline to obtain a positive electrode active material.
[0006] According to the preparation method of the above embodiment of the present invention, polyaniline, an oxidant and water are mixed, the pH value is adjusted to acidic, and an oxidation reaction is performed. Under acidic conditions, the oxidant can convert the imine group Oxidation Structure, get Then the oxidized polyaniline is mixed with an alkaline solution for reaction. The alkaline treatment can Convert to structure, containing Finally, the intrinsically oxidized polyaniline is used as a positive electrode active material to prepare a positive electrode, and an electrochemical cell is assembled with an electrolyte containing lithium ions to perform electrochemical reduction. During the electrochemical reduction process, The nitrogen atom in the structure has a lone pair of electrons and can form a coordination bond with the lithium ion to obtain The structure of the polyaniline molecule is then reduced The structure becomes The structure realizes the embedding of lithium ions, and the interaction between the embedded lithium ions and polyaniline can form a stable charge storage site, which can store more charge, thereby improving the specific capacity of the positive electrode active material. As a result, the positive electrode active material exhibits a higher specific capacity.
[0007] In addition, the method according to the above embodiment of the present invention may also have the following additional technical features:
[0008] In some embodiments of the present invention, the molar ratio of the polyaniline to the oxidant is 1:(2-5). This is conducive to obtaining a positive electrode active material with a higher specific capacity.
[0009] In some embodiments of the present invention, the oxidant includes at least one of hydrogen peroxide and potassium permanganate. This is conducive to obtaining a positive electrode active material with a higher specific capacity.
[0010] In some embodiments of the present invention, the pH value is 0-2. This is conducive to obtaining a positive electrode active material with a higher specific capacity.
[0011] In some embodiments of the present invention, the oxidation temperature is 25° C.-60° C. As a result, the collision between the oxidant and the benzene ring and nitrogen atom on the polyaniline molecular chain is more frequent and intense, thereby more easily inducing the oxidation reaction, which is conducive to obtaining a positive electrode active material with a higher specific capacity.
[0012] In some embodiments of the present invention, the oxidation time is 12 hours to 48 hours, thereby increasing the degree of oxidation of polyaniline and facilitating obtaining a positive electrode active material with a higher specific capacity.
[0013] In some embodiments of the present invention, the electrochemical reduction includes constant voltage reduction, so that the electrochemical reduction reaction can be continuously and stably carried out, so that more lithium ions can be embedded in the polyaniline, thereby increasing the degree of lithiation of the polyaniline, and obtaining fully or highly lithiated polyaniline, thereby increasing the specific capacity of the polyaniline.
[0014] In some embodiments of the present invention, the constant voltage is 0.2 V-0.8 V. Thus, lithiated polyaniline can be obtained, which is beneficial to improving the specific capacity of the positive electrode active material.
[0015] In some embodiments of the present invention, the specific current at the end of the constant voltage reduction is less than 5 mA / g. Thus, lithiated polyaniline can be obtained, which is beneficial to improving the specific capacity of the positive electrode active material.
[0016] In some embodiments of the present invention, the molar concentration of the substance providing the lithium ions in the electrolyte is not less than 1 mol / L. Thus, a lithium ion source can be provided for the subsequent electrochemical reduction process, and lithiated polyaniline can be obtained, which is beneficial to improving the specific capacity of the positive electrode active material.
[0017] In some embodiments of the present invention, the material providing the lithium ions includes at least one of lithium chloride, lithium sulfate, lithium trifluoromethanesulfonate, lithium bromide and lithium hydroxide.
[0018] In some embodiments of the present invention, the electrolyte further includes zinc ions. Thus, the addition of zinc salt can adjust the conductivity of the electrolyte, accelerate the flow of electrons and ions inside the battery, make it easier for lithium ions to migrate from the electrolyte to the positive electrode (polyaniline electrode), and then embed into the molecular chain of polyaniline to form lithiated polyaniline, which can increase the specific capacity of the positive electrode active material.
[0019] In some embodiments of the present invention, the molar concentration of the substance providing the zinc ions is not greater than 0.5 mol / L. Thus, the intercalation efficiency of lithium ions can be improved, lithiated polyaniline can be obtained, and the specific capacity of the positive electrode active material can be improved.
[0020] In some embodiments of the present invention, the substance providing the zinc ions includes at least one of zinc oxide, zinc bromide, zinc trifluoromethanesulfonate, zinc sulfate and zinc chloride.
[0021] In the second aspect of the present invention, the present invention provides a positive electrode active material, which is prepared by the above-mentioned method. Therefore, the positive electrode active material has a higher specific capacity.
[0022] In some embodiments of the present invention, in the positive electrode active material, the percentage of nitrogen atoms having N-Li structure to the total nitrogen atoms is 70%-100%, thereby increasing the specific capacity of the positive electrode active material.
[0023] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0025] Figure 1 A comparison diagram of the charge and discharge curves of the positive electrode active materials of Example 1 and Comparative Example 1 is shown;
[0026] Figure 2 The CV curve of the positive electrode active material of Example 1 in an organic electrolyte is shown. DETAILED DESCRIPTION
[0027] Embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0028] Polyaniline is a type of high molecular conductive polymer with high electrochemical activity and specific volume. This type of polymer can usually be prepared by oxidative polymerization under acidic conditions. According to the different oxidation degrees of the structural polymerization units, it can be divided into an oxidized state composed of quinone structural units and a reduced state composed of phenolic structural units. In general, polyaniline prepared by oxidative polymerization has two oxidation state structures at the same time. During the polymerization process, the polyaniline molecular chain is doped with the acid anions in the solution to form doped polyaniline. The doped anions can be separated by alkali treatment to form polyaniline base, that is, intrinsic polyaniline. As shown below:
[0029]
[0030] The nitrogen atom in the oxidation unit of polyaniline base is only connected to the carbon on the benzene ring and does not contain the NH structure. The nitrogen atom in the reduction unit is connected to a hydrogen atom in addition to the carbon on the benzene ring and contains the NH structure. The theoretical specific capacity of polyaniline can exceed 290Ah / Kg, and it has good conductivity. It is an excellent electrochemical active material for the positive electrode of secondary batteries. When polyaniline base is used as the positive electrode active material of lithium-ion batteries, only The structure and lithium ion formation structure, and then restored, The structure becomes structure. The above reaction cannot occur. This reaction mechanism is shown in the figure below:
[0031] Reactions can occur:
[0032]
[0033] The reaction cannot occur:
[0034]
[0035] However, this positive electrode active material, on the one hand, makes it impossible to form a full battery with negative electrode materials that do not contain lithium, such as graphite, hard carbon, etc. On the other hand, even if it is used with a lithium-containing negative electrode, such as lithium metal, lithium alloy, etc., it will cause a drastic change in the concentration of the electrode liquid, which is not conducive to the stable operation of the battery, and the specific capacity of the positive electrode active material is low.
[0036] In view of this, in a first aspect of the present invention, the present invention provides a method for preparing a positive electrode active material. According to an embodiment of the present invention, the preparation method comprises:
[0037] S1. Mix polyaniline, an oxidant and water, adjust the pH value to acidic, and perform an oxidation reaction to obtain oxidized polyaniline.
[0038] In this step, polyaniline, an oxidant and water are mixed and the pH value is adjusted to an acidic state to perform an oxidation reaction. Under the acidic conditions and the action of the oxidant, the hydrogen ions (H + ) can enter the main chain of polyaniline and interact with the imine group The N atom in the amine reacts with the protonated polyaniline to obtain Structure of oxidized polyaniline.
[0039] It should be noted that the structure of polyaniline is mainly composed of benzene ring-quinone ring redox units connected alternately, as shown in the following figure:
[0040]
[0041] According to some specific embodiments of the present invention, the molar ratio of the polyaniline to the oxidant is 1:(2-5). For example, it can be 1:2, 1:3, 1:4, 1:5, etc. By limiting the molar ratio of polyaniline to the oxidant within the above range, the degree of oxidation of the polyaniline can be effectively increased to obtain highly oxidized polyaniline, which can change the molecular structure of the polyaniline and increase the electrochemical active sites in the polyaniline, so that the polyaniline can more effectively transfer and store charges during the electrochemical process, thereby facilitating the acquisition of a positive electrode active material with a higher specific capacity. Furthermore, extending the reaction time and increasing the reaction temperature can also increase the degree of oxidation of the polyaniline.
[0042] According to some specific embodiments of the present invention, the oxidant includes at least one of hydrogen peroxide and potassium permanganate.
[0043] According to some specific embodiments of the present invention, the pH value is 0-2. For example, it can be 0, 1, 2, etc. By limiting the pH value to the above range, under acidic conditions, the hydrogen ions (H + ) can enter the main chain of polyaniline and interact with the imine group The N atom in the amine reacts with the protonated polyaniline to obtain Thus, it is beneficial to obtain a positive electrode active material with a higher specific capacity.
[0044] According to some specific embodiments of the present invention, the oxidation temperature is 25° C.-60° C. For example, it can be 25° C., 30° C., 40° C., 50° C., 60° C. By limiting the oxidation temperature within the above range, the collision between the oxidant and the benzene ring and nitrogen atom on the polyaniline molecular chain is more frequent and intense, so that the oxidation reaction is more easily triggered, which is conducive to obtaining a positive electrode active material with a higher specific capacity.
[0045] According to some specific embodiments of the present invention, the oxidation time is 12h-48h. For example, it can be 12h, 15h, 20h, 30h, 40h, 48h, etc. By limiting the oxidation time to the above range, the oxidation degree of polyaniline can be increased, which is conducive to obtaining a positive electrode active material with a higher specific capacity.
[0046] S2, mixing the polyaniline oxide and an alkaline solution to react, so as to obtain the polyaniline oxide in an intrinsic state.
[0047] In this step, the oxidized polyaniline is mixed with an alkaline solution to react and dedope the polyaniline so that the hydrogen ions (H + ) and hydroxide ions (OH - ) to form water molecules, which can remove hydrogen ions and obtain Structure of the intrinsic state of oxidized polyaniline.
[0048] Optionally, in the alkaline solution, the molar concentration of the alkali is 1 mol / L. The degree of dedoping can be controlled to ensure that sufficient alkaline ions react with protons while avoiding excessive dedoping and maintaining the integrity of the polyaniline molecular chain. This is conducive to obtaining a positive electrode active material with a higher specific capacity.
[0049] As an example, the base includes, but is not limited to, at least one of sodium hydroxide and potassium hydroxide.
[0050] S3, using the intrinsic state polyaniline oxide as a positive electrode active material to prepare a positive electrode.
[0051] In this step, the positive electrode is prepared by using intrinsic polyaniline oxide as the positive electrode active material. Specifically, the intrinsic polyaniline oxide, a conductive agent, lithium chloride and water are mixed to form a uniform suspension, the suspension is coated on the current collector by a doctor blade method to form a uniform coating, and then dried to obtain the positive electrode.
[0052] Optionally, the conductive agent includes but is not limited to at least one of carbon black, conductive graphite and carbon nanotubes.
[0053] S4, using a solution containing lithium ions as an electrolyte, assembling it with the positive electrode into an electrochemical cell, and performing electrochemical reduction, so that the lithium ions are doped into the intrinsic state of the oxidized polyaniline to obtain a positive electrode active material.
[0054] In this step, the positive electrode, the separator and the counter electrode obtained in step S3 are sequentially loaded into an electrolytic cell, an electrolyte containing lithium ions is added to the electrolytic cell to form an electrochemical cell, and electrochemical reduction is performed so that the lithium ions can be embedded in the intrinsic oxidized polyaniline. After the reduction is completed, the positive electrode is taken out, washed with deionized water and ethanol, and then filtered and dried to collect the product to obtain lithiated polyaniline, thereby obtaining a positive electrode active material with a higher specific capacity.
[0055] Optionally, the membrane includes but is not limited to at least one of a filter paper membrane and a glass fiber membrane.
[0056] Optionally, the counter electrode includes but is not limited to at least one of zinc metal and iron metal.
[0057] According to some specific embodiments of the present invention, in the electrolyte, the molar concentration of the substance providing the lithium ions is not less than 1 mol / L. For example, it can be 1 mol / L, 3 mol / L, 5 mol / L, 7 mol / L, 8 mol / L, etc. By limiting the concentration of lithium ions within the above range, a lithium ion source can be provided for the subsequent electrochemical reduction process, and lithiated polyaniline can be obtained, which is beneficial to improve the specific capacity of the positive electrode active material.
[0058] As an example, the substance providing the lithium ions includes, but is not limited to, at least one of lithium chloride, lithium sulfate, lithium trifluoromethanesulfonate, lithium bromide and lithium hydroxide.
[0059] According to some specific embodiments of the present invention, the electrolyte further includes zinc ions. The addition of zinc ions is conducive to electrochemical corrosion of the zinc electrode, making it easier for zinc ions to enter the electrolyte, prompting lithium ions in the electrolyte to migrate to the positive electrode (polyaniline electrode), which is conducive to the embedding of lithium ions into the molecular chain of polyaniline to form lithiated polyaniline, and can improve the specific capacity of the positive electrode active material.
[0060] According to some specific embodiments of the present invention, in the electrolyte, the molar concentration of the substance providing the zinc ions is not greater than 0.5 mol / L. For example, it can be 0.1 mol / L, 0.2 mol / L, 0.3 mol / L, 0.4 mol / L, 0.5 mol / L, etc. By limiting the molar concentration of the zinc salt within the above range, it is beneficial to electrochemically corrode the zinc electrode, making it easier for the zinc ions to enter the electrolyte, promoting the migration of lithium ions in the electrolyte to the positive electrode (polyaniline electrode), which is beneficial for the lithium ions to be embedded in the molecular chain of polyaniline to form lithiated polyaniline, and can improve the specific capacity of the positive electrode active material.
[0061] As an example, the substance providing the zinc ions includes, but is not limited to, at least one of zinc oxide, zinc bromide, zinc trifluoromethanesulfonate, zinc sulfate, and zinc chloride.
[0062] According to some specific embodiments of the present invention, the electrochemical reduction includes constant voltage reduction. On the one hand, the constant voltage electrochemical reduction process can control the insertion rate of lithium ions, so that lithium ions are inserted into the polyaniline molecular chain at a relatively stable rate, which is conducive to forming a uniform lithiated polyaniline structure. On the other hand, under constant voltage, the electrochemical reduction reaction can be carried out continuously and stably, so that more lithium ions can be inserted into the polyaniline, thereby increasing the degree of lithiation of the polyaniline, and being able to obtain fully or highly lithiated polyaniline, thereby increasing the specific capacity of the polyaniline.
[0063] According to some specific embodiments of the present invention, the constant voltage is 0.2V to 0.8V. For example, it can be 0.2V, 0.4V, 0.5V, 0.6V, 0.8V, etc. By limiting the constant voltage within the above range, the transfer of electrons can be promoted, the rate of the reduction reaction can be increased, and the reduction reaction can be made more thorough, avoiding the initiation of side reactions, and increasing the degree of lithiation of polyaniline, thereby obtaining a positive electrode active material with a higher specific capacity.
[0064] When the electrode containing intrinsically oxidized polyaniline is used as the positive electrode, zinc metal is used as the counter electrode, and the electrolyte is a mixture of 5 mol / L lithium chloride and 0.1 mol / L zinc chloride, the process of electrochemical reduction is as follows:
[0065] positive electrode:
[0066] negative electrode:
[0067] During the electrochemical reduction reaction, as the positive electrode is reduced and consumes lithium ions, the lithium ion concentration in the electrolyte decreases; the zinc at the negative electrode is converted into zinc ions, and the zinc ion concentration in the electrolyte increases.
[0068] According to some specific embodiments of the present invention, the specific current at the end of the constant voltage reduction is less than 5 mA / g. During the constant voltage reduction, as the reduction process proceeds, the current gradually decreases, and when the current is less than a certain value, the reaction can be considered complete. Therefore, by limiting the specific current at the end of the constant voltage reduction to the above range, the reduction reaction can be considered to be completed, and lithiated polyaniline is obtained.
[0069] It should be noted that the specific current refers to the current passing through a unit mass of the positive electrode active material.
[0070] According to the preparation method of the embodiment of the present application, polyaniline, an oxidant and water are mixed and the pH value is adjusted to acidic, and the obtained mixed solution is oxidized. Under acidic conditions, the oxidant can convert the imine group Oxidation Structure, get The oxidized polyaniline is then mixed with an alkaline solution for dedoping, which can Convert to structure, so that polyaniline can be lithiated to obtain The intrinsic state oxidized polyaniline of the structure. Finally, in an electrolyte containing lithium ions, a positive electrode containing the intrinsic state oxidized polyaniline is used for electrochemical reduction. During the electrochemical reduction process, since the nitrogen atoms on the polyaniline molecular chain have lone pairs of electrons, they can form coordination bonds or ionic bonds with lithium ions, thereby realizing the embedding of lithium ions. The interaction between the embedded lithium ions and the polyaniline forms stable charge storage sites, which can store more charges, thereby increasing the specific capacity of the positive electrode active material. As a result, the positive electrode active material exhibits a higher specific capacity. In addition, the preparation process does not involve toxic raw materials, does not require the participation of organic solvents, does not have toxic and harmful and greenhouse gas emissions, and the material does not contain high-value heavy metals such as nickel and cobalt, and has good economic efficiency and high environmental safety. At room temperature, the preparation of the positive electrode active material can be completed without high-energy consumption conditions such as high-temperature heating, and the electrochemical reduction process is a spontaneous electrochemical reduction process without the need for additional external power supply.
[0071] In the second aspect of the present invention, the present application provides a positive electrode active material. According to an embodiment of the present invention, the positive electrode active material is prepared by the above method. Therefore, the positive electrode active material has a higher specific capacity.
[0072] According to some specific embodiments of the present invention, the positive electrode active material has The percentage of the number of nitrogen atoms in the structure to the total number of nitrogen atoms is 70%-100%. For example, it can be 70%, 80%, 90%, 100%, etc. The percentage of the number of nitrogen atoms in the structure to the total number of nitrogen atoms exceeds 70%, the degree of lithiation of the polyaniline is high, and the specific capacity of the positive electrode active material is improved.
[0073] It should be noted that the ratio of the amount of lithium to the amount of nitrogen in the positive electrode active material is the degree of lithiation of the positive electrode active material.
[0074] The scheme of the present disclosure will be explained below in conjunction with the examples. Those skilled in the art will appreciate that the following examples are only used to illustrate the present disclosure and should not be considered to limit the scope of the present disclosure. Where specific techniques or conditions are not indicated in the examples, the techniques or conditions described in the literature in this area or the product instructions are used. Where the manufacturers of reagents or instruments are not indicated, they are all conventional products that can be obtained commercially.
[0075] Example 1
[0076] (1) 5 g of freshly prepared polyaniline was added to 150 mL of a 10% hydrogen peroxide aqueous solution, and the pH value of the system was adjusted to ≤1 with concentrated hydrochloric acid. After stirring at room temperature for 12 hours, the mixture was filtered and collected to obtain oxidized polyaniline.
[0077] (2) The oxidized polyaniline is mixed with a sodium hydroxide solution having a molar concentration of 1 mol / L to react, thereby obtaining the oxidized polyaniline in an intrinsic state.
[0078] (3) The intrinsic oxidized polyaniline and carbon black are mixed in a ratio of 9:1, and a lithium chloride aqueous solution with a molar concentration of 1 mol / L is added to the mixture at a mass ratio of 20%. After ultrasonic treatment, a uniform suspension is formed. After a portion of the suspension is taken to form a uniform coating on a carbon paper substrate by a doctor blade method, the coating is vacuum dried at 100°C to obtain a polyaniline electrode. The polyaniline electrode is used as a positive electrode, and the glass fiber diaphragm and the metal zinc foil counter electrode are used as negative electrodes. The electrolytic cell is sequentially loaded. An electrolyte (a mixture of lithium chloride with a molar concentration of 5 mol / L and zinc chloride with a molar concentration of 0.1 mol / L) is added to the electrolytic cell, and after complete infiltration, a constant voltage reduction is performed at a voltage of 0.5 V. When the specific current is less than 5 mA / g, the reduction is completed, the positive electrode is taken out, washed with deionized water and ethanol, filtered, dried and collected to obtain a positive electrode active material.
[0079] The positive electrode active material of Example 2-11 is the same as that of Example 1 except that some experimental parameters are different from those of Example 1.
[0080] Some experimental parameters of the positive electrode active materials of Examples 1-11 are shown in Table 1.
[0081] Table 1
[0082]
[0083] Note: "Zn / Zn under neutral conditions 2+ vsSHE = -0.76 V" means that under neutral conditions, the zinc electrode (Zn 2+ The potential difference between it and the standard hydrogen electrode (SHE) is -0.76.
[0084] Comparative Example 1
[0085] Step (3) in Example 1 was deleted, and steps (1) and (2) in Example 1 were retained. The remaining experimental parameters were the same as those in Example 1.
[0086] Comparative Example 2
[0087] Step (1) and step (2) in Example 1 were deleted, step (3) in Example 1 was retained, and the remaining experimental parameters were the same as those in Example 1.
[0088] Testing and analysis
[0089] Under the same conditions, the positive electrode active materials of Examples 1-11 and Comparative Examples 1-2 were subjected to a lithiation degree test and a cyclic voltammetry (CV) test, respectively. The specific test methods are as follows:
[0090] Lithiation degree test: The positive electrode active material obtained in Example 1 was used as the positive electrode and lithium titanate (Li 4 Ti 5 O 12 ) is used as the negative electrode of the battery. The positive and negative electrode reactions of the battery are as follows:
[0091] positive electrode:
[0092] negative electrode:
[0093] Among them, due to lithium titanate (Li 4 Ti 5 O 12 ) is a negative electrode material that does not provide lithium ions to the positive electrode. The lithium ions in the reaction can only be provided by the polyaniline lithium positive electrode. Therefore, it can be used to evaluate the degree of lithiation of the positive electrode, where the degree of lithiation = specific capacity / theoretical specific capacity of complete lithiation (290 mAh / g) × 100%.
[0094] Figure 1 The charge and discharge curve comparison diagram of the battery of Example 1 and Comparative Example 2 is shown. The positive electrode active material of Example 1 has a high specific capacity, while the positive electrode active material of Comparative Example 2 has almost no capacity.
[0095] Cyclic voltammetry (CV) test: A two-electrode button cell test was used, with lithium polyaniline as the positive electrode, lithium titanate as the negative electrode, and an electrolyte with a concentration of 1 mol / L (LiPF 6 , a mixture of ethylene carbonate and dimethyl carbonate). Constant current charge and discharge were performed at a current of 50 mA / g, and the voltage range was 0.8V to 2.3V. The average specific capacity of 5 consecutive charge and discharge cycles from the 2nd to the 6th cycle was taken as the test result.
[0096] Figure 2 The CV curve of the positive electrode active material of Example 1 in an organic electrolyte is shown. From the figure, it can be seen that the lithiated polyaniline has a significant redox peak and good reversibility.
[0097] The test results are shown in Table 2.
[0098] Table 2
[0099]
[0100]
[0101] “ / ” means none.
[0102] Combining Table 1 and Table 2, it can be seen that compared with Comparative Examples 1-2, the positive electrode active materials obtained in Examples 1-11 have a higher degree of lithiation and a higher specific capacity.
[0103] Comparative Example 1 is a polyaniline material that has not been lithiated, has almost no battery capacity, and can only provide limited capacity (3.2 mAh / g) through the capacitor effect.
[0104] Comparative Example 2 is a common polyaniline material that has not been oxidized, and has a low degree of lithiation (<50%), and cannot provide a high specific capacity.
[0105] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", "some implementation schemes" or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, unless they are contradictory.
[0106] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A method for preparing a positive electrode active material for a lithium ion battery, characterized in that: include: Mixing polyaniline, an oxidant and water, adjusting the pH value to acidic, and performing an oxidation reaction to obtain oxidized polyaniline; The polyaniline oxide and an alkaline solution are mixed and reacted to obtain the polyaniline oxide in an intrinsic state; The intrinsic state polyaniline oxide is used as a positive electrode active material to prepare a positive electrode; A solution containing lithium ions is used as an electrolyte, and the electrolyte is assembled with the positive electrode to form an electrochemical cell, and electrochemical reduction is performed to allow lithium ions to be doped into the intrinsically oxidized polyaniline to obtain a positive electrode active material.
2. The preparation method according to claim 1, characterized in that: The molar ratio of the polyaniline to the oxidant is 1:(2-5); and / or, The oxidant includes at least one of hydrogen peroxide and potassium permanganate.
3. The preparation method according to claim 1, characterized in that: The pH value is 0-2.
4. The preparation method according to claim 1, characterized in that: The oxidation temperature is 25°C-60°C; and / or, The oxidation time is 12h-48h.
5. The preparation method according to claim 1, characterized in that: The electrochemical reduction includes constant voltage reduction.
6. The preparation method according to claim 5, characterized in that: The constant voltage is 0.2V-0.8V; and / or, The specific current at the end of the constant voltage reduction is less than 5 mA / g.
7. The preparation method according to claim 1, characterized in that: In the electrolyte, the molar concentration of the substance providing the lithium ions is not less than 1 mol / L; and / or, The material providing the lithium ions includes at least one of lithium chloride, lithium sulfate, lithium trifluoromethanesulfonate, lithium bromide and lithium hydroxide.
8. The preparation method according to claim 1, characterized in that: The electrolyte further includes zinc ions; and / or, The molar concentration of the substance providing the zinc ions is not greater than 0.5 mol / L; and / or, The substance providing the zinc ions includes at least one of zinc oxide, zinc bromide, zinc trifluoromethanesulfonate, zinc sulfate and zinc chloride.
9. A positive electrode active material for a lithium ion battery, characterized in that: The positive electrode active material is prepared by the preparation method described in claims 1-8.
10. The positive electrode active material according to claim 9, characterized in that In the positive electrode active material, the percentage of nitrogen atoms with N-Li structure to total nitrogen atoms is 70%-100%.
